The mercantile effect : art and exchange in the Islamicate world during the 17th and 18th centuries - Babaie, Sussan; Gibson, Melanie (Gingko Library art series., 2017)
"The ten essays in this volume introduce a fascinating array of subjects, each one exploring an aspect of the far-reaching 'mercantile effect' and it's impact across western Asia in the early modern era. In the seventeenth and eighteenth centuries the increased movement of merchants and merchandise from China to Europe brought desirable exotic commodities to new markets but also spread ideas, tastes and technologies across western Asia as never before."--Jacket